Who's coming to the rescue? Revenue-sharing slumps and implicit bailouts during the Great Recession - Dirk Foremny; Albert Solé-Ollé (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
This paper analyzes the distribution of discretionary transfers from higher tiers of government in the process of fiscal adjustment in local jurisdictions which were hit by a negative revenue shock in formula transfers. Spanish local governments experienced a 30% fall in their revenue-sharing revenues at the beginning of the Great Recession. We use a 'difference-in-discontinuities' design to identify the causal effect of that shock on the amount of discretionary grants provided by three higher tiers of government (i.e., central, regional, and provincial) and on other budget items (i.e., spending and taxation). We identify these effects using an exogenous variation in formula transfers, as the losses during the crisis of municipalities above the 5,000 population threshold were greater than the losses of those below this threshold. We find that, on average, municipalities above and below the 5,000 inhabitant threshold did not differentially adjust their budgets during the crisis. Rather, we find that for themost indebted municipalities, a substantial share of the shock was absorbed by discretionary grants provided by regional and provincial governments.
urn:nbn:de:bsz:180-madoc-413804
Keywords: E62; H72; R5; 330; intergovernmental transfers; bailouts; fiscal consolidation